Phenomenon of digital da’wah: Analysis of religious moderation and the ethics of da’wah communication on social media - Nase, Nase; Holina, Holina; Syah, Yoshy Hendra Hardiyan (Jurnal Ilmu Dakwah, 2025)
Purpose – This study analysis the phenomenon of digital da'wah, focusing on religious moderation and the ethics of da'wah communication using a virtual ethnographic approach. Two controversial case studies are presented in this study: Gus Miftah and an iced tea seller, as well as da'wah in unconventional spaces (Bethel Indonesia Church and a nightclub). Method – This study uses a qualitative, virtual ethnographic approach to analyse the phenomenon of digital da'wah on social media. Result – The research findings show that, First, the implementation of religious moderation in digital da'wah requires a more careful approach in balancing freedom of expression with social responsibility. Second, Preachers need to develop digital competencies that include not only technical skills, but also an understanding of digital communication ethics and the social impact. Third, the role of social media algorithms in shaping public perception of da'wah messages is crucial. Implication – This research contributes to the development of a framework for ethical and moderate digital da'wah. Originality/Value – This study examines the phenomenon of digital da'wah in the era of social media with a focus on religious moderation (digital wasathiyyah) and ethics of da'wah communication. *** Tujuan – Studi ini menganalisis fenomena da'wah digital, dengan fokus pada moderasi agama dan etika komunikasi da'wah menggunakan pendekatan etnografi virtual. Dua studi kasus yang kontroversial dipresentasikan dalam studi ini: Gus Miftah dan penjual teh es, serta da'wah di ruang-ruang tidak konvensional (Gereja Bethel Indonesia dan klub malam). Metode – Studi ini menggunakan pendekatan etnografi virtual kualitatif untuk menganalisis fenomena da'wah digital di media sosial. Hasil – Temuan penelitian menunjukkan bahwa, Pertama, implementasi moderasi agama dalam da'wah digital memerlukan pendekatan yang lebih hati-hati dalam menyeimbangkan kebebasan berekspresi dengan tanggung jawab sosial. Kedua, para da'wah perlu mengembangkan kompetensi digital yang mencakup tidak hanya keterampilan teknis, tetapi juga pemahaman tentang etika komunikasi digital dan dampaknya terhadap masyarakat. Ketiga, peran algoritma media sosial dalam membentuk persepsi publik terhadap pesan dakwah sangat krusial. Implikasi – Penelitian ini berkontribusi pada pengembangan kerangka kerja untuk dakwah digital yang etis dan moderat. Orisinalitas/Nilai – Studi ini mengkaji fenomena dakwah digital di era media sosial dengan fokus pada moderasi agama (digital wasathiyyah) dan etika komunikasi dakwah.